Ammonothermal Crystal Growth of Functional Nitrides for Semiconductor Devices: Status and Potential - Wostatek, Thomas; Chirala, Venkata Yogananda Maruthi Rajesh; Stoddard, Nathan; Civas, Ege Noyan; Pimputkar, Siddha; Schimmel, Saskia (Materials, 2024)
The state-of-the-art ammonothermal method for the growth of nitrides is reviewed here, with an emphasis on binary and ternary nitrides beyond GaN. A wide range of relevant aspects are covered, from fundamental autoclave technology, to reactivity and solubility of elements, to synthesized crystalline nitride materials and their properties. Initially, the potential of emerging and novel nitrides is discussed, motivating their synthesis in single crystal form. This is followed by a summary of our current understanding of the reactivity/solubility of species and the state-of-the-art single crystal synthesis for GaN, AlN, AlGaN, BN, InN, and, more generally, ternary and higher order nitrides. Investigation of the synthesized materials is presented, with a focus on point defects (impurities, native defects including hydrogenated vacancies) based on GaN and potential pathways for their mitigation or circumvention for achieving a wide range of controllable functional and structural material properties. Lastly, recent developments in autoclave technology are reviewed, based on GaN, with a focus on advances in development of in situ technologies, including in situ temperature measurements, optical absorption via UV/Vis spectroscopy, imaging of the solution and crystals via optical (visible, X-ray), along with use of X-ray computed tomography and diffraction. While time intensive to develop, these technologies are now capable of offering unprecedented insight into the autoclave and, hence, facilitating the rapid exploration of novel nitride synthesis using the ammonothermal method.<br
Keywords: ammonothermal; synthesis; nitrides; semiconductors; solubility; in situ monitoring; crystal; high-pressure technology; supercritical fluid; GaN

Emerging research directions in the field of nitride semiconductors - Wostatek, Thomas; Civas, Ege Noyan; Zheng, Jun; Chirala, Venkata Yogananda Maruthi Rajesh; Schimmel, Saskia (13th annual meeting of the young crystal growers (jDGKK), 2025)

Fundamentals of ammonothermal growth of nitride crystals - Chirala, Venkata Yogananda Maruthi Rajesh; Schimmel, Saskia (12th Annual jDGKK Meeting, 2024)